Income Tax as an Instrument for Preventing Money Laundering from the Perspective of Pancasila Justice - Eddie Bachtiar Siagian; Mulyono; John Pieris (MSJ : Majority Science Journal, 2025)
Pancasila is the foundational ideology and moral compass of the Indonesian nation, serving not only as the basis of national identity but also as the supreme legal foundation for the formation and implementation of laws and regulations in Indonesia. In the context of law enforcement in the field of taxation, Pancasila must be the primary reference, especially in efforts to position tax law as a strategic instrument in the prevention of money laundering crimes. Conceptual reflections on the role of tax law in combating money laundering need to be examined thoroughly, particularly by analyzing the changes occurring in both fundamental and organic tax regulations. These changes must be capable of identifying and addressing various legal issues that arise, both from normative and implementation perspectives. In this regard, the Government of the Republic of Indonesia has both a moral and constitutional obligation to ensure that every tax policy and regulation implemented remains grounded in the values of justice, humanity, and mutual cooperation as reflected in the principles of Pancasila. Thus, the application of tax law as a means of preventing money laundering should not only be repressive but must also reflect a fair and civilized legal system. This effort is expected to realize a tax system that is not only effective and efficient but also aligned with the noble ideals of the Indonesian nation, leading to good governance that is clean, transparent, and socially just for a better Indonesia in the future.